NOP2/Sun RNA methyltransferase 2 promotes tumor progression via its interacting partner RPL6 in gallbladder carcinoma. Issue 11 (23rd September 2019) - Gao, Yuan; Wang, Zheng; Zhu, Yidi; Zhu, Qin; Yang, Yang; Jin, Yunpeng; Zhang, Fei; Jiang, Lin; Ye, Yuanyuan; Li, Huaifeng; Zhang, Yichi; Liang, Haibin; et al.
Abstract: NOP2/Sun domain family, member 2 (NSUN2) is a nuclear RNA methyl‐transferase catalyzing 5‐methylcytosine formation. Evidence shows that NSUN2 is correlated with cell unlimited proliferation. However, its functional role in gallbladder carcinoma (GBC), which is the most common biliary tract malignancy and has a poor prognosis, remains to be determined. Here we found that NSUN2 was highly expressed in GBC tissues as well as cell lines. NSUN2 silencing repressed GBC cell proliferation and tumorigenesis both in vitro and in vivo. Conversely, upregulation of NSUN2 enhanced GBC cell growth and colony formation. We further discovered that RPL6 was a closely interacting partner with NSUN2. Silencing RPL6 resulted in insufficient NSUN2 translational level and accumulative NSUN2 transcriptional level. Exogenous expression of NSUN2 partially rescued the effect of RPL6 in gallbladder cancer progression. Taken together, our data provided novel mechanic insights into the function of NSUN2 in GBC, thus pointing to NSUN2 as a potential and effective therapeutic approach to GBC treatment. Abstract : The highly expressed NSUN2 promotes GBC proliferation and tumorigenesis both in vitro and in vivo. Ribosomal protein L6 (RPL6), an interacting partner of NSUN2, orchestrates with NSUN2 in GBC progression through partial involvement in its translation process. This study describes the function of NSUN2 in GBC, indicating it as a potential therapeutic approach to the disease.